Liberalization: The key to unlocking natural gas potential in Brazil? - Liliana Diaz (The Oxford Institute for Energy Studies, 2021)
Brazil holds great promise for natural gas development: a large population underpinning rising energy demand; sizeable reserves, and a market hungry for diversification of energy sources. While great progress has been achieved in the last 30 years in the development of natural gas production, infrastructure and demand, the Brazilian gas market remains in its infancy with respect to its potential. After six years of attempting comprehensive reform, in April of 2021, a new gas law was enacted (2021 Gas Law). The expectation is that this law and its implementing regulation will not only cement the reform providing legal security to investors but will help address obstacles that so far have prevented market expansion. It is expected that the new regulatory framework, and accompanying market design, will pave the way to a liquid and competitive market. In light of this, two important questions come to mind: can liberalization single-handedly effect the required market transformation and can liberalization be implemented within the constrained window afforded by energy transition? This paper examines the challenges and opportunities the Brazilian natural gas reform and liberalization process brings. It starts with an overview of the gas market; it then briefly chronicles the reform efforts, covering their rationale as well as the main features of the recently approved 2021 Gas Law -and its expected benefits; the third section focuses on critical aspects in future market development such as offshore reserve gas monetization, transport and import infrastructure development and new demand outlets; the fourth section details the proposed market design and the focus of regulatory developments in the short term and the last section of the paper offers some concluding thoughts and points to relevant topics for a future research agenda.
Keywords: 330; 2021 Gas Law; Brazil; Competition; Energy Transition; Gas Market; Liberalisation; Natural gas; Petrobras; Regulation